"Does it have to be a real story?" A social semiotic assessment of an emergent writer. (2nd September 2020) - Kesler, Ted
ABSTRACT: Standardized writing assessments based in linear progressions position teachers for deficit views of young children's emergent writing development. Consequently, the researcher video recorded a writing assessment of his son, Daniel, at age 5 years, 4 months, as he composed a story across pages of a blank book, using an assortment of writing tools. Data sources included the transcription of the writing session and Daniel's final product. The researcher first used open coding then coding based in systemic functional linguistics. Based in ecological and social semiotic perspectives, the researcher shows how Daniel's writing development was expressed interpersonally, with the emerging text functioning as mediational tool. Findings show Daniel's emergent sense of self as a writer, the role of the adult facilitator, and the dynamics of interaction and dialectic of Daniel's internalization process. As formative assessment, next steps in instruction are suggested. The author discusses the necessities of closely observing and supporting young children's composing process and the imperative of a developmental assets perspective when assessing young children's writing, with implications for policy, teacher education, teaching, and research.